Assistance of Natural Handmade Soap Production to Darul Ibadah Community Bangkok for saving Environment and Financial Issue - Mutoharoh Mutoharoh; Luluk Muhimatul Ifada; Naila Najihah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Consumption of skincare products is potential causing environmental and personal financial problems. Most of the skincare products are packaged in plastic materials and contain hazardous chemicals. Besides, the price of high-quality skincare is generally expensive, and some people may not be able to afford it. The world community must be aware that their self-care should not impact big problems. This program aims to assist the community in producing natural handmade soap as one of a skincare series in various regions, and for this time, the main partner of this program is the Darul Ibadah community in Phutthabucha , Thung Khru District, Bangkok. This activity was carried out as part of a collaborative agreement between the Faculty of Economics, Sultan Agung Islamic University and Kasetsart University. This assistance is expected to be an effort to save the community by creating their own qualified products, reducing waste and water pollution from chemical-based soaps